(untitled) (Communication & Society, 2013)
Communication is widely accepted as central to the construction of institutional image and organizational culture. In this sense, new technologies are playing a significant role in the development of new institutional communication (IC) instruments which contribute to the achievement of these IC objectives. Some of these tools are sometimes deemed soft instruments because they are supposed to require little involvement of the institution board. However, institutional image is such a sensitive asset that soft instruments may entail serious consequences for institutions. This paper aims at directing attention to the relevance of these tools by describing their implications. In so doing, we address institutional videos known as lipdubs.